Frontal Medial Theta-Based Intelligence System for Verifying Mild Traumatic Brain Injury - Pankaj Kumar Sahu; Karan Jain (Frontiers in Biomedical Technologies)
Purpose: The purpose of this study was to create an Intelligence System (IS) to analyze the Electroencephalogram (EEG) characteristics of patients with mild Traumatic Brain Injury (mTBI) and healthy volunteers. Generally, mTBI research demonstrates that patients suffer from Working Memory (WM). The frontal cortex is involved in the clinical physiology of mTBI and is crucial for delayed memory.